Entomologische Chronik (Ralph Leonard Coe). - Smith, Kenneth G. V.; Morge, Günter (Beiträge zur Entomologie = Contributions to Entomology, 1970)
In memoriam Ralph Leonard Coe, M. I. Biol., *16.03.1906 +13.03.1968.